Four New Steroidal Glycosides, Protolinckiosides A – D, from the Starfish Protoreaster lincki. Issue 8 (1st August 2016) - Malyarenko, Timofey V.; Kicha, Alla A.; Kalinovsky, Anatoly I.; Ivanchina, Natalia V.; Popov, Roman S.; Pislyagin, Evgeny A.; Menchinskaya, Ekaterina S.; Padmakumar, Krishna Pillai; Stonik, Valentin A.
Abstract : Four new steroidal glycosides, protolinckiosides A – D (1 –4, resp.), were isolated along with four previously known glycosides, 5 –8, from the MeOH/EtOH extract of the starfish Protoreaster lincki . The structures of1 –4 were elucidated by extensive NMR and ESI‐MS techniques as (3 β, 4 β, 5 α, 6 β, 7 α, 15 α, 16 β, 25 S )‐4, 6, 7, 8, 15, 16, 26‐heptahydroxycholestan‐3‐yl 2‐ O ‐methyl‐ β ‐d ‐xylopyranoside (1 ), (3 β, 5 α, 6 β, 15 α, 24 S )‐3, 5, 6, 8, 15‐pentahydroxycholestan‐24‐yl α ‐l ‐arabinofuranoside (2 ), sodium (3 β, 6 β, 15 α, 16 β, 24 R )‐29‐( β ‐d ‐galactofuranosyloxy)‐6, 8, 16‐trihydroxy‐3‐[(2‐ O ‐methyl‐ β ‐d ‐xylopyranosyl)oxy]stigmast‐4‐en‐15‐yl sulfate (3 ), and sodium (3 β, 6 β, 15 α, 16 β, 22 E, 24 R )‐28‐( β ‐d ‐galactofuranosyloxy)‐6, 8, 16‐trihydroxy‐3‐[(2‐ O ‐methyl‐ β ‐d ‐xylopyranosyl)oxy]ergosta‐4, 22‐dien‐15‐yl sulfate (4 ). The unsubstituted β ‐d ‐galactofuranose residue at C(28) or C(29) of the side chains was found in starfish steroidal glycosides for the first time. Compounds1 –4 significantly decreased the intracellular reactive oxygen species (ROS) content in RAW 264.7 murine macrophages at induction by proinflammatory endotoxic lipopolysaccharide (LPS) from E . coli . Abstract : Four New Steroidal Glycosides, Protolinckiosides A – D, from the Starfish Protoreaster lincki T. V. Malyarenko, A. A. Kicha*, A. I. Kalinovsky, N. V. Ivanchina, R. S. Popov, E. A. Pislyagin, E. S. Menchinskaya, K. P. Padmakumar, V. A. Stonik*